Digital needs & gaps assessment for farmer producer organizations in Maharashtra, India - Nagaraji, Satish; Kajale, Dilip; Malik, Sushant; Kadam, Sachin (CGIAR, 2023)
The Digital Innovation in Agriculture workshop was centred on bolstering digital capabilities within Farmer Producer Organizations (FPOs) and nurturing collaborations with Disruptive Agricultural Technology start-ups. The event, held in Pune, convened FPOs, digital innovators, and experts to explore digital needs, promote digital innovation awareness, and foster FPOinnovator partnerships. Interactive sessions emphasized the adoption of key technologies, continuous stakeholder interaction, and consortium-based approaches, aiming to demonstrate digitalization's value and transparent collaboration frameworks. The workshop also recognized the constraints in perspective coverage and discussion depth, offering a foundation for future initiatives to scale effective models and cultivate a dynamic ecosystem for collaboration in the agricultural digital landscape.